3.
2)
а) (a-b)-(c-d)=a-b-c+d
б) (a-b)+(c-d)=a-b+c-d
в) x-(a-b)+(c-d)=x-a+b+c-d
г) 10-(a-b)-(c+d)=10-a+b-c-d
4.
1)
а) 3b+(5a-7b)=-4b+5a
б) -3q-(8p-3q)=-8p
в) 5x+(11-7x)=-2x+11
г) -(8c-4)+4=-8(c-1)
a) (a-b)-(c-d) = a-b-c+d
б) (a-b)+(c-d) = a-b+c-d
в) x-(a-b)+(c-d) = x-a+b+c-d
г) 10-(a-b)-(c+d) = 10-a+b-c-d
а) 3b+(5a-7b) = -4b+5a
б) -3q-(8p-3q) = -3q-8p+3q = -8p
в) 5x+(11-7x) =5x-7x+11 = -2x +11
г) -(8c-4)+4 = -8c+4+4 = -8c+8 = -8(c-1)
3.
2)
а) (a-b)-(c-d)=a-b-c+d
б) (a-b)+(c-d)=a-b+c-d
в) x-(a-b)+(c-d)=x-a+b+c-d
г) 10-(a-b)-(c+d)=10-a+b-c-d
4.
1)
а) 3b+(5a-7b)=-4b+5a
б) -3q-(8p-3q)=-8p
в) 5x+(11-7x)=-2x+11
г) -(8c-4)+4=-8(c-1)
a) (a-b)-(c-d) = a-b-c+d
б) (a-b)+(c-d) = a-b+c-d
в) x-(a-b)+(c-d) = x-a+b+c-d
г) 10-(a-b)-(c+d) = 10-a+b-c-d
4)а) 3b+(5a-7b) = -4b+5a
б) -3q-(8p-3q) = -3q-8p+3q = -8p
в) 5x+(11-7x) =5x-7x+11 = -2x +11
г) -(8c-4)+4 = -8c+4+4 = -8c+8 = -8(c-1)